Treatment of disseminated ocular melanoma with sequential fotemustine, interferon α, and interleukin 2 - Becker, Jürgen C.; Schadendorf, Dirk (British journal of cancer, 2002)
Malignant melanoma of the uvea is remarkable for purely haematogenous dissemination and its tendency to metastasise to the liver. Although the liver is involved in up to 95% of patients, 50% of these also develop extrahepatic metastases, most often in the lungs, bone, skin, and brain. The only effective treatments reported to date relied on hepatic arterial chemoembolisation or -perfusion. The objective of this study was to establish a therapy protocol addressing patients with both sole liver involvement and systemic disease. Forty-eight patients with metastatic ocular melanoma received fotemustine 100 mg m−2 either as 60-min infusion into the hepatic artery or as 15-min infusion via a peripheral vein, depending on the metastatic sites involved, i.e., restriction to the liver or hepatic together with extrahepatic disease. For the first treatment cycle this infusion was repeated after one week. For all cycles, subsequent to a three week resting period, patients received an immunotherapy consisting of subcutaneous interleukin 2 and interferon α2. Although objective responses were more frequent within the cohort receiving intraarterial fotemustine (21.7 vs 8%), this difference did not translate into a significant benefit in overall survival, i.e., 369 and 349 days, respectively. Of note, this overall survival is much longer than that repeatedly reported for stage IV uveal melanoma not treated with fotemustine, suggesting a therapeutic activity of this cytostatic drug even after systemic administration.